Comparing Test‐Taking Behaviors of English Language Learners (ELLs) to Non‐ELL Students: Use of Response Time in Measurement Comparability Research. Issue 1 (29th November 2021) - Guo, Hongwen; Ercikan, Kadriye
Abstract : In this report, we demonstrate use of differential response time (DRT) methodology, an extension of differential item functioning methodology, for examining differences in how students from different backgrounds engage with assessment tasks. We analyze response time data from a digitally delivered mathematics assessment to examine timing differences between English language learner (ELL) and non‐ELL student groups. When matched on the total sum scores of the studied item form, results showed that ELLs spent a significantly longer time on most items compared to the non‐ELLs who performed similarly on the test form. When matched on the total response time, results showed that ELL students spent a significantly longer time on items in the first half of the form but a shorter time on items in the second half. This research demonstrates the usefulness of DRT methodology in gaining insights about the differential engagement of students with assessment tasks. Abstract : Report Number: RR‐21‐25